The socioemotional challenges and consequences for caregivers of Aboriginal and Torres Strait Islander children with otitis media: A qualitative study. (16th March 2022) - Campbell, Letitia; Reath, Jennifer; Hu, Wendy; Gunasekera, Hasantha; Askew, Deborah; Watego, Chelsea; Kong, Kelvin; Walsh, Robyn; Doyle, Kerrie; Leach, Amanda; Tyson, Claudette; Abbott, Penelope
Abstract: Introduction: Living with ear disease can have extensive impacts on physical, emotional and social well‐being. This study explored otitis media (OM) and its management from the perspective of caregivers of Aboriginal and Torres Strait Islander children. Methods: Semi‐structured interviews were conducted from 2015 to 2020 with caregivers of Aboriginal and Torres Strait Islander children with OM. Thematic analysis of transcripts was undertaken using a constructivist grounded theory approach through the leadership and the cultural lens of an Aboriginal community‐based researcher. Results: Caregivers described OM as having profound impacts on their child's physical, developmental, and emotional well‐being, with long waits for specialist treatment contributing to extra strain on families. Children's well‐being suffered when OM was mistaken for poor behaviour and children were punished, with caregivers subsequently experiencing strong feelings of guilt. Concerns were conveyed about the social implications of having a sick child. The variable nature of OM symptoms meant that caregivers had to monitor closely for sequelae and advocate for appropriate treatment. Success in navigating the diagnosis and treatment of OM can be strongly impacted by the relationship between caregivers and health professionals and the perceived access to respectful, collaborative and informative healthcare. Conclusion: OM may have substantial social and emotional consequences for children and their caregivers. A holistic understanding of the way in which OM impacts multiple facets of health and well‐being, as well as recognition of challenges in accessing proper care and treatment, will aid families managing OM and its sequelae. Patient or Public Contribution: Governing boards, managers, staff and community members from five Australian Aboriginal Medical Services were involved in the approval, management and conduct of this study and the wider clinical trials. The caregivers of Aboriginal and Torres Strait Islander patients at these services informed the interview study and guided its purpose.